Measuring health workers’ motivation composition: validation of a scale based on self-determination theory in Burkina Faso - Lohmann, Julia; Souares-Coutant, Aurélia; De Allegri, Manuela (Human resources for health, 2017)
Although motivation of health workers in low- and middle-income countries (LMICs) has become a topic of increasing interest by policy makers and researchers in recent years, many aspects are not well understood to date. This is partly due to a lack of appropriate measurement instruments. This article presents evidence on the construct validity of a psychometric scale developed to measure motivation composition, i.e., the extent to which motivation of different origin within and outside of a person contributes to their overall work motivation. It is theoretically grounded in Self-Determination Theory (SDT).
Gesehen am 09.06.2017